Newer Perspectives of Mechanisms for Euglycemic Diabetic Ketoacidosis - Xiaofang Yu; Saifei Zhang; Long Zhang (International Journal of Endocrinology)
Euglycemic diabetic ketoacidosis (EDKA) was considered a rare condition with its specific definition and precipitating factors. However, with the wide use of sodium glucose cotransporter 2 (SGLT-2) inhibitors, the newest class of antidiabetic agents, EDKA has come back into the spotlight. Relevant cases are increasingly being reported along with insights into the mechanism of EDKA. It seems increasingly clear that EDKA is more common than we used to believe. The SGLT-2 inhibitor-associated EDKA also indicates a necessary review of our previous understanding of “diabetic” ketoacidosis, since the SGLT-2 inhibitor predisposes patients to DKA in a “starvation” way. Actually, there are growing reports about starvation-induced ketoacidosis as well. The previously “exclusive” nomenclature and cognition of these entities need to be reexamined. That the hormonal interactions in DKA may differ from the severity of insulin deficiency also may have served in the scenario of EDKA. The SGLT-2 inhibitors are newly approved in China. The main purpose of this work is to have a better understanding of the situation and update our knowledge with a focus on the pathogenesis of EDKA.